Pengaruh Literasi Wakaf, Tingkat Religiusitas, Pendapatan terhadap Minat Berwakaf Uang (Studi Kasus Masyarakat Kelurahan Indarung Kecamatan Lubuk Kilangan Kota Padang) - Ingra Sovita; Dinda Yulia Putri (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
Cash waqf has significant potential as an Islamic philanthropic instrument to enhance social welfare; however, its realization remains relatively low, indicating limited public interest in participating in cash waqf. This study aims to analyze the influence of waqf literacy, religiosity, and income on the intention to perform cash waqf among the community of Indarung Subdistrict, Lubuk Kilangan District, Padang City. The research employs a quantitative approach using a survey method involving 220 respondents selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) with the assistance of SmartPLS software. The results reveal that waqf literacy and religiosity have a positive and significant effect on the intention to perform cash waqf, while income does not show a significant influence. The coefficient of determination (R²) value of 0.545 indicates that these three variables collectively explain 54.5% of the variation in public intention to participate in cash waqf. These findings imply that improving waqf literacy and strengthening religious values are important strategies to increase community participation in cash waqf